"You don't take anything for granted": The role of anthropology in improving services, policies, and parenting practices for adoptive families. Issue 2 (November 2015) - ROMÁN, BEATRIZ SAN; GAGGIOTTI, HUGO; MARRE, DIANA
Abstract : This article examines the impact of the transnational adoption research of an interdisciplinary group of researchers (AFIN). Since 2004, AFIN has successfully developed several research projects with the participation of practitioners and adoptive families and their associations. AFIN uses an ethnographic method and an anthropological perspective—which provides insights on transnational adoption, politics, and professional culture in Spain. This combination has resulted in a substantial body of knowledge as well as the recognition of opportunities for and challenges to building bridges among academics, policy makers, practitioners, and adoptive families in order to increase the wellbeing of families. We suggest that engagement and collaboration with family associations might offer the best chance for social anthropological research to have an influence on family public policies and practices in Spain.